Pandemics and Firms : Drawing Lessons from History - Cevik, Serhan (IMF Working Papers; Working Paper, 2020)
The global economy is in the midst of an unprecedented slump caused by the COVID-19 pandemic. To assess the likely evolution of nonfinancial corporate performance going forward, this paper investigates empirically the impact of past pandemics using firm-level data on more than 537,000 companies from 14 developing countries during the period 1998-2018. The analysis indicates that the prevalence of infectious diseases has an economically and statistically significant negative effect on nonfinancial corporate performance. This adverse impact is particularly pronounced on smaller and younger firms, compared to larger and more established corporations. We also find that a higher number of infectious-disease cases in population increases the probability of failure among nonfinancial firms, particularly for small and young firms. In the case of COVID-19, the magnitude of these effects will be much greater, given the unprecedented scale of the outbreak and strict policy responses to contain its spread.